Persicaria odorata as a fly repellent - Yaacob, Yanti; Jon, Nazwa; Salleh, Nunshaimah (2024)
Flies belong to the order Diptera and are insects with one pair of membrane wings, little, club-like hind wings called halters, big compound eyes, and short, simple antennae, body hair and legs are covered with tiny hair that carry illness. Due to the transfer of illnesses, which includes the spread of cholera by flies in many developing nations, several species of Diptera are crucial vectors for the transmission of various pathogens, making their control a key focus in public health efforts aimed at reducing the incidence of waterborne and foodborne diseases. They can spread germs to food or surfaces in a matter of seconds. As a result, illness transmission has a negative effect on society's health as well as the environment. According to a study, Vietnamese coriander or Persicaria ordorata can work as a fly repellent to help with this issue. This study aims to investigate the potential of Persicaria ordorata towards repelling flies in UiTM Tapah cafetria. Three conditions are examined for Persicaria ordorata which are fresh leaf, dried grinded leaf and pure essential oil. The most effective method of using the Persicaria ordorata would have to be the pure essential oil method due to the number of flies that is trapped is low. The dried leaf sample method is the least effective, so it can be said that it may not be the best way to repel flies because the compounds that were meant to do so either did not exist or may have evaporated into the surrounding air while the sample was drying in the sun. While the fresh leaf sample has outperformed the dried sample in terms of fly repellent properties, this approach is still not the most efficient.